Mahkamah Konstitusi dalam Sistem Ketatanegaraan Republik Indonesia - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Candra Wijaya; Muhammad Syafiq Mustofa; Salman Abdurrosyid (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
The Constitutional Court is a state institution that emerged from the amendments to the 1945 Constitution, as part of the efforts to strengthen the principles of the rule of law and constitutional democracy in Indonesia. This institution plays a crucial role in upholding legal regulations, ensuring proper checks, and balancing the power between institutions and the state. This research aims to examine the position, authority, and contributions of the Constitutional Court within Indonesia's governance system. A normative approach is generally used, along with analyses of laws, Constitutional Court decisions, and various related legal literature. The results of the study show that the Constitutional Court not only acts as the gatekeeper of the structure, but also as the sole translator of the structure, which has an important influence on the dynamics of relations between state institutions and the development of constitutional law in Indonesia. The Constitutional Court participates in the protection of citizens' rights, the improvement of the electoral system, and the upholding of the principles of democracy and real justice.